Memahami Makna Penanda Visual Pada Patung Bambu Karya Joko Dwi Avianto - Sumarwahyudi (Institut Seni Indonesia Denpasar, 2009)
There are a number of methods can be applied in giving critics on fine art, one of which is through the art- lover oriented approach. Basically this approach gives emphasis on the meaning of art work is fully determined by the appreciator or the lover himself/herself. This kind of approach has lately become popular particularly in order to understand the meaning of a contemporary art work. Joko Dwi Avianto’s bamboo statue “Harmony of Speed” which is used as the topic of this article is seen by the writer from his own viewpoint as an appreciator of art. The exploration of meaning for this art work makes use of Roland Barthes’ connotative semiotic approach. The connotative meaning of the statue is related to the adoption of modern civilization in traditional life. Facing the modern life, artist community cannot directly refuse or accept it instantly. They should accommodate both aspects (modern and tradition) proportionally. One compromise step is that whatsoever decision you take in art creation, one thing that you should be kept in mind is that you never neglect your own cultural identity.